Explaining the Informal Economy: an Exploratory Evaluation of Competing Perspectives - Williams, Colin (Relations industrielles / Industrial Relations, 2015)
The aim of this paper is to conduct an exploratory analysis of the wider economic and social conditions associated with larger informal economies. To do this, three competing perspectives are evaluated critically which variously assert that cross-national variations in the size of the informal economy are associated with: under-development (modernization perspective); high taxes, corruption and state interference (neo-liberal perspective), or inadequate state intervention to protect workers (political economy perspective). Analyzing the variable size of the informal economy across 33 developed and transition economies, namely 28 European countries and five other OECD nations (Australia, Canada, Japan, New zealand and the USA), the finding is that larger informal economies are associated with under-development as measured by lower levels of GNI per capita, employment participation rates, average wages and the institutional strength and quality of the bureaucracy, higher levels of perceived public sector corruption, lower levels of expenditure on social protection and labour market intervention to protect vulnerable groups, but also restrictions on the use of temporary employment contracts and TWAs. The outcome is a tentative call to combine a range of tenets from all three perspectives in a new more nuanced and finer-grained understanding of how the cross-national variations in the size of the informal economy are associated with broader economic and social conditions. The paper concludes by discussing the implications for theory and policy, including the need for further analysis of the different impacts on the size of the informal economy of a wider range of indicators of modernization, corruption, taxation and types of state intervention.